SirPROM: Sistema de Recomendaç˜ao de Promoç˜oes Multicrit´erio para Supermercados - Jos´e Gildo de Ara´ujo J´unior; Cleyton Rage de Assunç˜ao (Anais do Encontro de Computação do Oeste Potiguar ECOP/UFERSA (ISSN 2526-7574), 2020)
This work aims develop SirPROM a multicriteria promotion recommendation system in order to automate suggested sales between products available in a supermarket aiming at the gradual control of stock, reduction of waste and the consequent increase in revenue. The administrative sector of many supermarkets, disregards the economic potential present in the purchase records of their customers and suppliers stored over time. From the processing of these data emerges the understanding of innumerable patterns hitherto unknown, among them the association rules of items sold and customers’ shopping preferences in order to promote the expansion of billing.